A fenomenologia estética em Michel Henry: a arte como revelação da vida invisível - Padilha, Jéssica Coimbra (2018)
This work presents the aesthetics in Michel Henry, in order to demonstrate that art is the revelation of the invisible life through a phenomenological perspective. For Michel Henry, art does not imitate life, it unveils what is invisible from the sensible. In order to demonstrate this, the author has as influence and inspiration Kandinsky, who affirmed that the laws of painting occur in life and not in the representation or imitation thereof by the objectivity. Thus Michel Henry, with his phenomenology of life and subjectivity, believes that art is an inner resonance, free from the figure of a particular object. Thus, the place of development of aesthetics is the invisible life. In this sense, life, because it is invisible, experiences itself, because that is its essence, to feel itself in full subjectivity through the body. Thus, it is in the theoretical writings of the painter Kandinky that the author has substance to carry out his phenomenological aesthetics.